Development of mathematics learning module based on mind-mapping on opportunity materials - Trisna Rukhmana; Loria Wahyuni (Journal of Educational and Learning Studies, 2020)
Based on the results of observations made at SMA N 5 Sungai Penuh known that in the mathematics learning process students do not understand the learning material well, the ability of students to develop material concepts and solve problems in the form of practice questions given by the teacher is still lacking, students are lacking of self-confidence to ask if there is material that has not been understood, students also cannot develop their thinking ideas creatively. This means that the ability to think creatively and critically of students has not developed optimally. The specific purpose of this research is to develop and produce teaching materials in the form of mind mapping-based modules for learning mathematics, which are valid, practical and effective and can increase students' motivation, activities and learning outcomes, especially in the material opportunities. This development research consists of four stages, namely; the define stage, the design stage, the develop stage and the disseminate stage. The validation results with the valid category indicated by an average value of 76%. The practicality results with the practical category are shown by an average value of 75.3%. Effectiveness results with the effective category in terms of the aspects of activity, student motivation, and from the aspect of achievement of learning outcomes.